Controversies of Ontological Hermeneutics: A Practical Aspect - Daraškevičiūtė, Vaiva (Problemos, 2015)
This paper discusses two versions of ontological hermeneutics. One concept of ontology is represented by Hans-Georg Gadamer, and another is represented by two Italian thinkers – Luigi Pareyson and Gianni Vattimo. These three philosophers share a belief that in post-metaphysical thought ontology is possible only as practical hermeneutics. However, the Italian philosophers Pareyson and Vattimo attain the practical approach in a different way than Gadamer. This paper states that the views herewith distinguished, i.e., those of Gadamer and Pareyson-Vattimo, are different in two aspects. The first difference is related to the manner these authors construct their concepts of hermeneutics. Gadamer sees hermeneutical ontology as a universal theory of understanding, whereas according to Pareyson and Vattimo we encounter a theory of interpretation. This aspect supposes the second point by which the distinction between the position of Gadamer and that of Pareyson and Vattimo becomes even clearer. The second difference is related to the manner they describe the praxis itself. In Gadamer’s philosophy hermeneutical praxis is, first of all, the dialogue which leads to understanding, whereas for Pareyson and Vattimo the hermeneutical praxis means the conflict.